2019
DOI: 10.3390/ani9090686
|View full text |Cite
|
Sign up to set email alerts
|

The Endocannabinoid System of Animals

Abstract: Simple SummaryOur understanding of the Endocannabinoid System of animals, and its ubiquitous presence in nearly all members of Animalia, has opened the door to novel approaches targeting pain management, cancer therapeutics, modulation of neurologic disorders, stress reduction, anxiety management, and inflammatory diseases. Both endogenous and exogenous endocannabinoid-related molecules are able to function as direct ligands or, otherwise, influence the EndoCannabinoid System (ECS). This review article introdu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 84 publications
1
49
0
10
Order By: Relevance
“…In summary, the pattern of distribution of cannabinoid receptors in the GASH/Sal is highly similar to that described in other mammal species (Freundt-Revilla et al, 2017;Silver, 2019).…”
Section: Non-neuronal Cellssupporting
confidence: 80%
“…In summary, the pattern of distribution of cannabinoid receptors in the GASH/Sal is highly similar to that described in other mammal species (Freundt-Revilla et al, 2017;Silver, 2019).…”
Section: Non-neuronal Cellssupporting
confidence: 80%
“…To make it even more complex, PEA's action on PPAR-α is also responsible for increasing CB2 expression and TRPV1 activation [92,93]. It is now clear that PEA is an endocannabinoid-related compound, sharing metabolic pathways and targets with the endocannabinoid system, which is now considered to play an integral role in maintaining body homeostasis [94]. Most notably, the heterogeneous family of canonical and putative cannabinoid receptors, i.e., PEA targets, are being extensively studied in companion animals and their distribution has been found in several body tissues [95][96][97][98][99][100][101][102][103][104][105][106][107][108][109].…”
Section: Pea Mechanism Of Action: a Multitarget Redundancymentioning
confidence: 99%
“…Research has indicated an extensive endocannabinoid system in animals, comprised of systemic endogenous ligands and receptors with critical localization to nervous tissue in both the central nervous system and the immune system (Donvito et al 2017;Fitzcharles et al 2016;Silver 2019;Walker et al 2019). The primary function of the endocannabinoid system in humans is to maintain homeostasis, which includes regulation of pain and inflammation (Fitzcharles et al 2016;Guindon and Hohmann 2009;Silver 2019). The endocannabinoid system is integral to normal physiological functioning in humans and has been associated with the pathology of several neurological conditions (Russo 2016).…”
Section: Endocannabinoid System and Pain Managementmentioning
confidence: 99%